Literasi Digital Marketing Sebagai Upaya Peningkatan Penjualan Pada Paguyuban UMKM Kecamatan Serang Baru Kabupaten Bekasi - Indra Permana,; Asral, Asral; Endah Yaodah Kodratila,; Maha Putra, (Joong-Ki : Jurnal Pengabdian Masyarakat, 2023)
Internet now provides many conveniences in human life. Almost all human activities always use the internet, from communication to education, including work. Information spreads fairly quickly with the internet and various supporting media platforms. With this convenience, not everyone can use the internet well. Most young people use the internet simply for entertainment. If it is used wisely, it will have a good impact, one of which is as a medium for learning entrepreneurship and marketing. Small Medium Enterprises (SME) prepares people to have work-ready skills in their field of knowledge about create product and sale to a market. A few SME not become successful entrepreneurs. Therefore, digital marketing as a strategy needs to be introduced to vocational students, especially in this case Community of SME which previously had never held this counseling. The purpose of this activity is for SME to recognize the benefits of the internet as a digital means to market products, services, or other things and to generate entrepreneurial motivation from an early age.